The Isolation of, and Cytodifferentiation of a Mucor species as Affected by Nitrogen Source and Elevated Temperature (Global Journal of Science Frontier Research, 2015)
Vegetative differentiation leading to dimorphic switching by filamentous microorganisms has drawn intense attention from scientists for a long time because of the central role played in the attempt to understand life processes, as well as the serious impacts exhibited in medicine, agriculture and industrial processes. A mucoraceous isolate, Mucor manihotis (tentative), from an agricultural niche was found to exhibit dimorphism in minimal medium; induced were thalloarthric-, holothallic-, holoblastic conidia as well as polar budding globose yeast cells when supplemented with ammonium sulphate or peptone as nitrogen source. Boxplot construction showed that peptone enhanced growth, but elevated temperature had profound morphogenetic effect as ovoidal and spindle shaped yeast cells additionally induced.
Keywords: mucor isolate; minimal medium; box plot; cytodifferentiation; cytoplasmic membrane; neoplastic units; binary protoplasts; yeast ontogeny; elevated tem